2014
DOI: 10.3168/jds.2014-8507
|View full text |Cite
|
Sign up to set email alerts
|

Application of liquid semen technology improves conception rate of sex-sorted semen in lactating dairy cows

Abstract: The objective was to compare reproductive performance of liquid sex-sorted (SS) semen with that of conventional (CON) semen in lactating dairy cows. Between 2011 and 2013, commercial dairy herds (n = 101, 203, and 253 for 2011, 2012, and 2013, respectively) with predominantly Holstein-Friesian cows were enrolled in a contract mating program to produce surplus heifers for export using liquid SS semen. During the spring mating period, each herd was allocated with liquid SS semen at 50% of its daily requirement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Using representative straws generated for the current study, Holden et al (2017) reported abnormally high levels of sperm agglutination (>20%) in both fresh SS treatments (SS-1M and SS-2M), which was associated with lower progressive motility. These high levels of agglutination could affect sperm transport to the site of fertilization, and they could have contributed to the somewhat lower reproductive performance achieved by the fresh SS treatments in the current study compared with Xu (2014).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Using representative straws generated for the current study, Holden et al (2017) reported abnormally high levels of sperm agglutination (>20%) in both fresh SS treatments (SS-1M and SS-2M), which was associated with lower progressive motility. These high levels of agglutination could affect sperm transport to the site of fertilization, and they could have contributed to the somewhat lower reproductive performance achieved by the fresh SS treatments in the current study compared with Xu (2014).…”
Section: Discussionmentioning
confidence: 81%
“…One significant weakness in most previously published studies on SS is the fact that treatments were applied to different ejaculates. Indeed, in some studies, different bulls were used for the SS and conventional treatments (Chebel et al, 2010;Xu, 2014); in others, different ejaculates from the same bull were used (De-Jarnette et al, 2009Norman et al, 2010). A recent trial in Germany (Lenz et al, 2016) aliquotted the ejaculate for the different SS treatments (n = 4), but used different contemporaneous ejaculates for the Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this technique in animals also raises great interest, both from scientific as well as economic point of view (9). Thus, the acceleration of reproduction management, the optimization of the biological and economic output at farm level and the improvement of genetic background are just some of the advantages that this technology could provide for live-stock -cattle - (10), swine - (11,12), sheep and goat farms (13).…”
Section: The Benefits Of Using Sexed Semenmentioning
confidence: 99%
“…Thus, the spread of artificial insemination with sexed semen brings about great advantages for both farm categories (10). It is estimated that by using these technologies, bovine meat production can reach a point where it can compete with chicken meat, both in terms of its nutritional qualities and its low production costs.…”
Section: The Benefits Of Using Sexed Semenmentioning
confidence: 99%